Individual Attention and Comprehension Identity Educators' ICT Competence on Indonesian Language Course with Integration of Multimedia at Secondary Education - Lira Hayu Afdetis Mana; Laspida Harti; Nurul Haniza Samsudin; Dina Ramadhanti; Rahayu Fitri (Lembaga Bale Literasi, 2026)
The integration of multimedia in secondary education promises increased attention and comprehension, yet classroom practice is often hindered by infrastructure readiness and educators' ICT competence. This research aims to: (1) map patterns of multimedia use by teachers; (2) identify barriers and institutional support; (3) assess students' attitudes and experiences toward multimedia-based learning; and (4) formulate recommendations for improving practice. A mixed methods approach was used through structured interviews with 53 teachers from 52 schools (total 424 response segments) and a 10-item Likert questionnaire with 49 students. Qualitative data were analyzed thematically (keyword/theme extraction), while quantitative data were analyzed descriptively; questionnaire reliability was calculated using Cronbach's ?. Results show the dominant theme of platforms (61.1%) with WhatsApp, video, and PowerPoint most frequently mentioned followed by benefits (47.9%), barriers (27.6%), and support (21.2%). Major barriers include device availability, internet access, and technical disruptions. Student attitudes were positive: composite mean 4.09 (SD 0.47) after reversing negative items; reliability ? = 0.76 (adequate). Pedagogically, teacher practices are primarily at the Substitution-Augmentation level (SAMR), which enhances presentation and material distribution; transformation of tasks toward Modification/Redefinition remains limited. Main recommendations include designing student product-based tasks, offline-first strategies, TPACK-based micro-PD, infrastructure standards and troubleshooting SOPs, and targeted content curation.